Vorausschauende Regelung von Fahrzeugsystemen durch stochastische Vorhersage der Fahrzeugdynamik - Fünfgeld, Sebastian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
Predictive control of vehicle systems often requires application of forecasting models. In this work a stochastic framework for generating forecasts of vehicle dynamics is proposed, to directly address uncertainty within the control algorithms. Building on this framework, the predictive control of vehicle systems with stochastic optimal control algorithms is investigated, implemented and evaluated for two exemplary vehicle systems.